2022
DOI: 10.3390/polym14235263
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Elastomeric Behavior of Polyglycine-Rich Regions of Spidroin 1 and 2 Proteins

Abstract: Two different polyglycine-rich fragments were selected as representatives of major ampullate gland spidroins (MaSp) 1 and 2 types, and their behavior in a water-saturated environment was simulated within the framework of molecular dynamics (MD). The selected fragments are found in the sequences of the proteins MaSp1a and MaSp2.2a of Argiope aurantia with respective lengths of 36 amino acids (MaSp1a) and 50 amino acids (MaSp2.2s). The simulation took the fully extended β-pleated conformation as reference, and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…The concept of hidden length implies that segments of the protein chains, originally in the amorphous phase, become progressively unfolded during stretching, but until a significant unfolding occurs, those segments do not play any relevant role in the mechanical performance of silk. In this regard, studies based on the Molecular Dynamics of the polyglycine fragments characteristic of the amorphous phase show that these fragments display an elastomeric behaviour [ 36 ], independently from the detailed conformation of the participating amino acids. Beyond a given value of true strain (or, correspondingly, of true stress) at which the unfolding of a fraction of those segments initially included in the hidden length takes place, the properties of the material are essentially determined by the behavior of this fraction of the chains.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of hidden length implies that segments of the protein chains, originally in the amorphous phase, become progressively unfolded during stretching, but until a significant unfolding occurs, those segments do not play any relevant role in the mechanical performance of silk. In this regard, studies based on the Molecular Dynamics of the polyglycine fragments characteristic of the amorphous phase show that these fragments display an elastomeric behaviour [ 36 ], independently from the detailed conformation of the participating amino acids. Beyond a given value of true strain (or, correspondingly, of true stress) at which the unfolding of a fraction of those segments initially included in the hidden length takes place, the properties of the material are essentially determined by the behavior of this fraction of the chains.…”
Section: Discussionmentioning
confidence: 99%
“…To expand and improve the applications of spider silk peptides and synthetic derivatives it is critical to understand and probe their mechanical properties and how these depend on molecular parameters and loading rates. To date, a few studies have tested the effects of design parameters like length and composition of peptide-based sensor linkers computationally or experimentally (28)(29)(30)(31). Some of these studies have revealed the mechanical effects of flow dependent stretching of spider silk, the influence of polyglycine regions and external forces on the elasticity of spider silk peptides, and details of fiber assembly.…”
Section: Introductionmentioning
confidence: 99%